The Effect of Storage Duration and Soaking of Eggs Using Basil Leaf Solution (Ocimum basilicum L.) on Maintaining the Internal Quality of Duck Eggs (Anas platyrhynchos domesticus) - Muhammad Umar Hakim Hakim; Nurzainah Ginting; Yunilas; Syaheera N Ibrahim (Jurnal Peternakan Integratif, 2025)
Duck eggs are highly nutritious animal based food products but are prone to quality deterioration during storage. One natural preservation method is immersion using basil leaf solution, which has antibacterial properties. This study aimed to determine the effect of storage duration and basil leaf solution concentration on the internal quality of duck eggs and to identify the most effective treatment combination. The research was conducted at the Livestock Production Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, using a factorial Completely Randomized Design (CRD) with two factors: basil solution concentration (0%, 15%, 30%, and 45%) and storage duration (0, 10, 20, and 30 days). Observed parameters included albumen index, yolk index, weight loss percentage, and pH value. The results showed a highly significant interaction (P<0.01) between the treatments on albumen index, yolk index, and pH. Immersion in 45% basil solution was effective in maintaining albumen and yolk indices as well as pH, while the 30% concentration was most effective in reducing weight loss. Day 10 was identified as the optimal storage period, during which all internal quality parameters remained stable. After this period, egg quality significantly declined.